Intelligent of Literacy Through Moderate Interpretation Strengthening Religious Moderation - Nini Arianti; Alfadilah Alfadilah Alfadilah; Faisal Faisal Faisal (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Another big problem worrying the Indonesian nation at this time is not only the Covid-19 pandemic. The reason is, when this epidemic hit, there were still acts of radicalism and terrorism. Unfortunately, this understanding that is vulnerable to infecting the younger generation is increasingly rampant in the midst of a pandemic. An individual becomes radically influenced by reading and experience. This enthusiasm was triggered by a wrong understanding of the verses of jihad. Radical behavior arises because of interpreting the meaning of the Qur'an and hadith which tend to be textual. Content that smells of religion but is wrapped in intolerance and radicalism is increasingly widespread. Meanwhile, millennials who are actively using social media are not literate yet. In this study, we used library research and a thematic method. We delve into and associate the ayat of the Qur’an to resolve the problem. It shows that the reading material and experience gained determines a person's understanding to be radical or moderate. This is in line with the opinion of experts that understanding the verses of the Qur'an to be more in-depth is understood by means of a contextualization approach. This approach does not only study from the aspect of language but from the socio-cultural aspect so that the verses of the Qur'an can be understood as a whole, not partially. Which is strengthening digital literacy through schools and colleges, socializing for the young generation, and holding training and discussion about it in schools and colleges